145k views
4 votes
Find the difference.
(4x2 - 6x+8) - (3x2 - 6x + 2)

Find the difference. (4x2 - 6x+8) - (3x2 - 6x + 2)-example-1
User Hanfei Sun
by
4.7k points

2 Answers

4 votes
Let's simplify step-by-step.
4
x
2

6
x
+
8

(
3
x
2

6
x
+
2
)
Distribute the Negative Sign:
=
4
x
2

6
x
+
8
+

1
(
3
x
2

6
x
+
2
)
=
4
x
2
+

6
x
+
8
+

1
(
3
x
2
)
+

1
(

6
x
)
+
(

1
)
(
2
)
=
4
x
2
+

6
x
+
8
+

3
x
2
+
6
x
+

2
Combine Like Terms:
=
4
x
2
+

6
x
+
8
+

3
x
2
+
6
x
+

2
=
(
4
x
2
+

3
x
2
)
+
(

6
x
+
6
x
)
+
(
8
+

2
)
=
x
2
+
6
User Mark Bolusmjak
by
5.2k points
3 votes

Answer:

x² + 6

Explanation:

(4x² -6x + 8 )- ( 3x² -6x +2 )

4x² -6x +8 - 3x² + 6x -2

now group like terms

4x² -3x² -6x +6x +8-2

⇒ x² +6

User Apar Adhikari
by
5.1k points